2021
DOI: 10.1021/acs.jpca.1c08105
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Wave Packet Treatment of Cold Nonadiabatic Reactive Scattering at the State-To-State Level

Abstract: Cold and ultracold collisions are dominated by quantum effects, such as resonances, tunneling, and nonadiabatic transitions between different electronic states. Due to the extremely long de Broglie wavelength in such processes, quantum reactive scattering is most conveniently characterized using the time-independent close-coupling (TICC) methods. However, the TICC approach is difficult for systems with a large number of channels because of its steep numerical scaling laws. Here, a recently proposed quantum wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 76 publications
1
15
0
Order By: Relevance
“…The TDWP method solves the time-dependent Schro ¨dinger equation by propagating a wave packet and features a better numerical scale (N log N) than the TICC method. As a result, the TDWP method is widely applied to the majority of triatomic [39][40][41] and polyatomic [42][43][44] reaction systems. However, for the calculations of cold and ultracold reaction dynamics, the conventional TDWP method is a great challenge due to the large de Broglie wavelength of ultracold molecules and the difficulty in absorbing the wave packet at the grid boundaries.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…The TDWP method solves the time-dependent Schro ¨dinger equation by propagating a wave packet and features a better numerical scale (N log N) than the TICC method. As a result, the TDWP method is widely applied to the majority of triatomic [39][40][41] and polyatomic [42][43][44] reaction systems. However, for the calculations of cold and ultracold reaction dynamics, the conventional TDWP method is a great challenge due to the large de Broglie wavelength of ultracold molecules and the difficulty in absorbing the wave packet at the grid boundaries.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Theoretically, the most reliable scheme for obtaining accurate dynamics data to study the collision mechanisms of a chemical reaction is to perform the dynamics calculations using the quantum mechanical method on a globally accurate PES. For the triatomic reactive systems, the TDWP method [23][24][25][26] is an efficient and powerful tool for studying reaction dynamics. Based on the newly constructed ground-state CaH 2 + PES, the quantum dynamics calculations of the Ca + ( 2 S) + H 2 (n 0 = 0, j 0 = 0) -CaH + + H reaction are carried out by the TDWP method to study the stateto-state dynamics.…”
Section: Quantum Dynamics Calculationsmentioning
confidence: 99%
“…In this study, a high-fidelity global PES of the ground-state (1 2 A 0 ) CaH 2 + is structured using the permutation invariant polynomial-neural network (PIP-NN) method 21,22 based on a large number of high-level ab initio points. Furthermore, the state-to-state quantum dynamics studies for the Ca + ( 2 S) + H 2 (n 0 = 0, j 0 = 0) -CaH + + H reaction are performed using the timedependent wave packet (TDWP) [23][24][25][26] calculations on this new PES. The remainder of this paper is organized as follows: Section 2 gives the computational details and the topographic characteristics of the ground-state CaH 2 + PES.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the energy is much lower than that of the crossing point, the GP effect still has a significant impact. Especially, recent theoretical works have shown that the GP effect in the reaction becomes dominant in the cold regime. , When the reaction contains electronically excited species, the nonadiabatic couplings must be included in the theoretical calculations due to the existence of electronic quenching channels, and the CI plays an important role in the collision mechanism. , Recently, the study of nonadiabatic electronic quenching of OH­( A 2 Σ) + H 2 shows that the anisotropic feature of PES makes the collision process mainly controlled by stereodynamics . In addition, for some reaction systems, although there is no CI between the excited-state and ground-state PESs, the nonadiabatic couplings between them still have an effect on the ground-state reaction dynamics . For the second kind of nonadiabatic process, the F/Cl ( 2 P 3/2 , 2 P 1/2 ) + H 2 /HD reactions are prototypes for studying spin–orbit coupling effects in reactions for a long time. ,− The relative reactivity of two spin–orbit states with H 2 /HD has been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…13 In addition, for some reaction systems, although there is no CI between the excited-state and groundstate PESs, the nonadiabatic couplings between them still have an effect on the ground-state reaction dynamics. 14 For the second kind of nonadiabatic process, the F/Cl ( 2 P 3/2 , 2 P 1/2 ) + H 2 /HD reactions are prototypes for studying spin−orbit coupling effects in reactions for a long time. 4,15−17 The relative reactivity of two spin−orbit states with H 2 /HD has been widely studied.…”
Section: Introductionmentioning
confidence: 99%